The Influence of The Saviter Learning Model on Student Learning Outcomes in Subtema 3 Ways to Maintain The Health of Human Blood Circulation Organs in Class V Sdn 091608 Sinaksak T.A 2023/2024 - Sundari; Rio Parsaoran Napitupulu; Kristianto Simarmata (International Journal of Integrated Science and Technology, 2023)
This research aims to determine whether there is an influence of the Make A Match learning model on student learning outcomes in theme 2 clean air for health, subtheme 2 the importance of clean air for breathing learning 1, and 2, in class V of SD Negeri 097320 Serapuh. The method used in this research is a pre-experimental quantitative approach using a one group pretest-posttest design. This research was carried out for 2 weeks starting from 2 September to 06 October 2023. The population in this research were all class V students at SD Negeri 097320 Serapuh with a total of 28 students who would be researched. The sample in this study was all students in class V of SD Negeri 097320 Serapuh with a total of 28 students consisting of 17 female samples and 11 male samples. The data collection techniques are tests and instrument trials. Based on the results of the data analysis tests carried out, the results of the normality test, homogeneity test and hypothesis test were obtained. From the results of the hypothesis test from the data analysis carried out, the results of the hypothesis test were obtained from the results of the tests given to students, so it was obtained, tcount 17.553 and ttable 2.056 with a significance level (2-tailed) 0.000, significant probability < 0.05, tcount > ttable = 17.553 > 2.056 So H0 is rejected and Ha is accepted. This explanation shows that there is an influence of the Make A Match learning model on student learning outcomes in theme 2 Clean air for health. Subtheme 2 The importance of clean air for breathing in class V SDN 097320 Serapuh.